2020
DOI: 10.1007/s13555-020-00436-1
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Evaluation of the Long-Term Safety and Efficacy of Infliximab in the Treatment Moderate-to-Severe Psoriasis

Abstract: Introduction: Psoriasis is a chronic immunemediated inflammatory skin disease that occurs in 2.5-3.5% of the general population. Infliximab (INF), a TNF-a inhibitor biologic agent, is a long-standing efficacious treatment for psoriasis; however, not all patients sustain a long-term response (LTR) because of a number of factors including antibody production. There is a paucity of studies assessing infliximab efficacy over a period C 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In the diet-induced obesity animal model, infliximab led to a reduction in the levels of blood glucose and insulin, and restored glucose homeostasis [57]. Surprisingly, patients with psoriasis with concomitant overweight or obesity are more likely to sustain the long-term response to infliximab than patients with normal weight for at least 5 years in a real-world study [58]. The dose of etanercept, adalimumab, and certolizumab pegol in the therapy of psoriasis is fixed, and their efficacy and safety are impaired by obesity.…”
Section: Tnf-α Inhibitorsmentioning
confidence: 97%
“…In the diet-induced obesity animal model, infliximab led to a reduction in the levels of blood glucose and insulin, and restored glucose homeostasis [57]. Surprisingly, patients with psoriasis with concomitant overweight or obesity are more likely to sustain the long-term response to infliximab than patients with normal weight for at least 5 years in a real-world study [58]. The dose of etanercept, adalimumab, and certolizumab pegol in the therapy of psoriasis is fixed, and their efficacy and safety are impaired by obesity.…”
Section: Tnf-α Inhibitorsmentioning
confidence: 97%
“…In addition, obesity makes the body enter a immunodepressive state, losing the normal immune response. 40 A retrospective multicenter study conducted in Italy reported that the mean PASI of the group with obesity with psoriasis was significantly higher than that of the non-obese group, and seemed to be related to the disease severity and the lower response to secukinumab. 41 Singh et al 42 also discovered that the treatment failure rate of anti-TNF therapy in patients who were overweight/ obese was 60% higher than that in normal cases, and even patients with obesity treated via weight-based regimens (such as infliximab) had an inferior response to therapy.…”
Section: Relationship Between Psoriasis and Obesity And Its Relevance...mentioning
confidence: 99%
“…Obesity changes the pharmacokinetics of drugs and increases the drug clearance, thus resulting in a shortened half-life and reduced serum concentration. In addition, obesity makes the body enter a immunodepressive state, losing the normal immune response 40 . A retrospective multicenter study conducted in Italy reported that the mean PASI of the group with obesity with psoriasis was significantly higher than that of the non-obese group, and seemed to be related to the disease severity and the lower response to secukinumab 41 .…”
Section: Relationship Between Psoriasis and Obesity And Its Relevance...mentioning
confidence: 99%
“…137,164 Infliximab, another TNF inhibitor, has also been shown to be effective in the treatment of paediatric psoriasis. [193][194][195][196] Infliximab is administered via intravenous infusion. 194 The recommended dose is 5 mg/kg at weeks 0, 2, and 6 and every 8 weeks thereafter.…”
Section: Fumaric Acid Estersmentioning
confidence: 99%